2012
DOI: 10.2495/fiva120161
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of volatile organic compounds emitted byThymus vulgaris

Abstract: Thymus vulgaris is a common Mediterranean vegetal species often involved in forest fires. The aim of this work is to characterize the VOCs emitted by the needles of this plant as functions of temperature. Experiments are performed using a flash pyrolysis apparatus. The influence of two parameters, namely the heating time and heating rate are studied: the highest VOCs' emissions are found for a heating time of 30 s at 5000 K/s. Two major compounds are identified for all the temperatures, thymol and p-cymene. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A number of reports on the essential oil composition of thyme leaves have been published. K. Chetehouna et al [4] identified and categorized the volatile compounds in thyme essential oil into 6 main groups: monoterpene, sesquiterpene, and oxygen derivatives composed of monoterpenic alcohol, monoterpenic phenol and monoterpenic ether. In addition, regardless of any variations in temperature and duration of the conducted experiments, the three main identified volatile components always were thymol, p-cymene and γ-terpinene.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports on the essential oil composition of thyme leaves have been published. K. Chetehouna et al [4] identified and categorized the volatile compounds in thyme essential oil into 6 main groups: monoterpene, sesquiterpene, and oxygen derivatives composed of monoterpenic alcohol, monoterpenic phenol and monoterpenic ether. In addition, regardless of any variations in temperature and duration of the conducted experiments, the three main identified volatile components always were thymol, p-cymene and γ-terpinene.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 We investigated in previous works the emissions of five Mediterranean vegetal species, namely, Rosmarinus officinalis, Pinus pinea, Thymus vulgaris, Lavandula stoechas, and Cistus albidus, at leaves scale using a flash pyrolysis apparatus. 4,22 R. officinalis has also been studied at plant scale. 3,23 In order to get validation elements for the AFF thermochemical approach, we measured in previous works combustion characteristics of the main BVOCs (a-pinene, limonene, p-cymene) emitted by fire-heated vegetation.…”
Section: Introductionmentioning
confidence: 99%